Pengaruh Inflasi, Suku Bunga BI Rate, Kurs Valuta Asing Dan Return On Assets (ROA) Terhadap Harga Saham Perusahaan Perbankan BUMN Yang Terdaftar Di Bursa Efek Indonesia - Sakinah; Pratiwi, Aliah (CV ODIS, 2024)
This research aims to determine the effect of inflation, Bl rate interest rates, foreign exchange rates and Return On Equity on share prices in state-owned banking companies listed on the IDX. The macro and micro economic environment is the environment that influences the company's daily operations. Investors' ability to understand and predict the company's macro and micro conditions in the future will be very useful in making profitable investment decisions. This research was conducted on state-owned banking companies listed on the IDX using annual reports for 2012-2022. The samples in this research were 4 banks, namely Bank Negara Indonesia Tbk, Bank Rakyat Indonesia Tbk, Bank Mandin Tbk and Bank Tabungan Negara Tbk. The sample was taken using a purposive sampling technique, namely taken based on criteria determined by the researcher. The data used is secondary data obtained from the company website and the Bl website. The data analysis method used in this research is the partial least squares (PLS) approach. Data processing uses SmartPLS software version 3.0. The results of this research are that inflation has an effect on stock prices, Bl rate, foreign exchange rates and Return on Assets have no effect on stock prices. Suggestions for future researchers are that they can use other variables and use different research periods.